Seasonal diversity, daily use and behaviour of birds using a green roof in a Mediterranean city - Álvaro Luna; Estel Blanch (Royal Society Open Science)
Urban green roofs offer environmental and social benefits and provide resources for urban wildlife; however, how birds use green roofs remains poorly studied in Mediterranean cities. Here, we develop a 1-year study in Madrid, Spain, recording the birds that use both an urban green roof and the adjacent conventional roofs throughout the four seasons. We recorded a total of 17 bird species in the area, of which 8 use the green roof surveyed. The most common species detected in both types of roofs was the feral pigeon (Columba livia), which exploited the green roof permanently, in contrast with the other species observed, which only appeared occasionally. We also found that more species visited the green roof in the central hours of the day and a higher richness of species in the spring. Moreover, we detect that most of the species were residents all year in the area and have granivorous or granivorous–omnivorous feeding habits. The main behaviour observed in the green roof was feeding, while no reproduction of any species was confirmed. We conclude that green roofs offer birds much-needed resources in metropolitan areas, promoting greener, more connected and more biodiverse cities.